Побудова системи ведення бухгалтерського обліку - Басюк, Тарас; Мицак, Василина; Одарченко, Віктор (Видавництво Львівської політехніки, 2014)
This article is about the problem of implementation of automation of accounting. Software, created for these purposes, has many advantages as well as disadvantages – it makes the company’s management to pay more attention to the choice of the software that would meet not only his requirements, but also would make possible to reduce the cost of its implementation.
Keywords: бухгалтерський облік; програмне забезпечення; підприємство; система; автоматизація